ON THE PHONOSTAISTICS OF THE LEILEK DIALECT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article explores the phonostatistics of the Leilek dialect, based on the collection of works «El Ichi - Önör Kenchi», which includes pieces by masters of song and storytelling arts. This study discusses the general phonostatistics of the Leilek dialect.
Keywords: epic «Manas», Leilek dialect, frequency, sounds, usage statistics